Effect of non surgical periodontal treatment on TNF-α levels in serum of patients with chronic periodontitis - Abdulhameed, Sazan Sartip; Nanakaly, Haween T. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Chronic periodontitis is a multifactorial inflammatory disease characterized by destruction of tooth supporting tissues. Tumor necrosis factor-α, a key inflammatory cytokine, plays an important role in periodontal destruction. This study aimed to analyze the effect of non-surgical periodontal treatment on tumor necrosis factor-α levels in serum of patient with chronic periodontitis (with and without using chlorhexidine 0.2% mouthwash). Methods: A total of 44 patients with moderate to severe localized chronic periodontitis were divided into: Group I (n=22) without using of chlorhexidine mouthwash and Group II (n=22) with 0.2% chlorhexidine mouthwash. Serum samples collected from each subjects at baseline and four weeks after scaling and root planning treatment were quantified for tumor necrosis factor-α levels using ELISA technique. Results: The mean concentration of TNF-α were significantly reduced one month after treatment in sera of patients with chronic periodontitis for group I when compared to its mean concentration before treatment (P <0.05), while in group II a highly significant reduction after one month treatment (P <0.001) was observed. Conclusion: The effect of non-surgical periodontal therapy with chlorohexidine mouth wash showed more reduction in the levels of serum tumor necrosis factor-α.